Dural arteriovenous fistula associated with intratumor hemorrhage. (January 2019) - Takemoto, Yushin; Kawano, Takayuki; Ohmori, Yuki; Nakagawa, Takashi; Ohta, Kazutaka; Kuroda, Jun-Ichiro; Yano, Shigetoshi; Mukasa, Akitake
Highlights: A 59-year-old woman presented with transient aphasia and dysgraphia. She had left anterior cranial fossa dAVF and a tumor with an intratumor hemorrhage. She underwent shunt-point extirpation for the dAVF and removal of the tumor. DAVF associated with intratumor hemorrhage is very rare condition. This dAVF may be due to the venous congestion of the tumor draining vein by the dAVF. Abstract: Dural arteriovenous fistula (dAVF) associated with an intracranial tumor is a relatively rare condition. Furthermore, to our knowledge, this is the first case report of dAVF associated with intratumor hemorrhage. We experienced this very rare case and report it here, along with a literature review. A 59-year-old woman presented with transient aphasia and dysgraphia. Computed tomography, magnetic resonance imaging, and angiography showed left anterior cranial fossa dAVF and a tumor with an intratumor hemorrhage. Cerebral angiography demonstrated AV shunts from the left ethmoidal artery via cortical vein flow into the superior sagittal sinus. She underwent shunt-point extirpation for the dAVF and removal of the tumor. The histological finding indicated transitional meningioma. The patient was discharged without any neurological deficit. A dAVF with intratumor hemorrhage is very rare and may be due to the venous congestion of the tumor draining vein by venous hypertension caused by the dAVF.